MANAGEMENT OF A CAT INFECTED WITH FELINE PANLEUKOPENIA VIRUS AND MYCOPLASMA HAEMOFELIS AT THE VETERINARY TEACHING HOSPITAL, HASANUDDIN UNIVERSITY - Muhammad Ayub; Musdalifah; Andi Rifqatul Ummah (Buletin Veteriner Udayana, 2026)
Infectious diseases in domestic cats (Felis catus) remain a major challenge in veterinary practice, particularly in multi-etiological infections involving viral agents and hemotropic parasites. Coinfection with Feline Panleukopenia Virus (FPV) and Feline Hemotropic Mycoplasmosis (FHM) can cause severe immunosuppression, exacerbate clinical signs, and increase mortality risk, often accompanied by complications such as feline flu due to opportunistic secondary infections. This study aimed to describe the clinical management of a feline flu case in a cat infected with FPV and concurrent FHM at the Veterinary Teaching Hospital, Hasanuddin University. This case report describes a domestic cat presenting with vomiting, hemorrhagic diarrhea, anorexia, dehydration, and respiratory distress. Diagnosis was established based on anamnesis, clinical examination, hematological analysis, FPV rapid testing, blood smear examination, and bacterial culture. Therapeutic management included fluid therapy, antiviral treatment, culture-guided antibiotic therapy, antiparasitic treatment, nebulization therapy using salbutamol, as well as supportive and nutritional care. The results revealed that the cat tested positive for FPV, Mycoplasma haemofelis was detected on blood smear examination, and Klebsiella pneumoniae was isolated through bacterial culture. Comprehensive therapeutic management led to gradual clinical improvement. This case highlights the importance of an integrated diagnostic and therapeutic approach in the management of multi-etiological infections in cats.